The Determinants of Parental Uptake of Childhood Immunization in Peri-Urban Areas of Karachi - A Cross-Sectional Study - Mawra Nawaz, Sameera Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Immunization is one of the simplest and cost-effective ways to protect a child from infectious diseases and mortality worldwide, and while global immunization coverage has increased dramatically the impact is low in developing countries like Pakistan, where many children remain unvaccinated or partially vaccinated. Aim: To determine the potential factors related to parents that impact the uptake of immunization in children living in the peri-urban area of Karachi, Pakistan. Methodology: An analytical cross-sectional study was conducted between Oct 2020 to May 2021. Purposive sampling technique based on the inclusion and exclusion criteria was used and a total of 100 parents of children were interviewed using the self-developed structured questionnaire focusing on factors like socio-demographic, parental health-seeking behavior, parental knowledge and perception of immunization and the reasons why a child is partially immunized. The data was collected from two EPI centers from the peri-urban area of Karachi to determine the parental factors associated with child immunization. Results: The results of the study show association between Child immunization and father occupation (p=0.000), parental education (p=0.000) and household income (p-value=0.000). history of sibling’s complete vaccination 35(70%), frequency of maternal antenatal visits 41(82%) accompanied by the husband 37 (74%) and have delivered the child in hospital 50(100%) by an obstetrician 50 (100) and for medical treatment child is always taken to a hospital 47(94%). Parents who consider vaccination important 48 (86%) with the significance of (p=0.001) and they have awareness regarding the total number of immunizations 38(76%) have fully immunized children. Conclusion: According to the study, parental education, occupation, income, health-seeking behavior, father’s involvement, child birth-related factors, parental awareness on immunization, perception of immunization